Single vein resection in surgery for pancreatic ductal carcinoma as a criterion of resectability - D. A. Chichevatov; V. V. Kalentjev; A. E. Glukhov (Сибирский онкологический журнал)
Background. Pancreatic ductal carcinoma (PDC) with involvement of the superior mesenteric vein (SMV) or/ and portal vein (PV) remains a discussible subject. We have evaluated vein invasion as a criterion of borderline resectability and long-term outcome. Material and methods. In our center, 68 patients underwent either 65 standard pancreatoduodenal resections or 3 pancreatoduodenectomies for PDC. Resection of SMV/PV was performed in 18 cases (26.5 %). Three patients received neoadjuvant chemotherapy (NACT), and adjuvant chemotherapy (ACT) was assigned to 37 patients (54.4 %). Results. Morbidity (42.0 vs 50.0 %, р=0.590) and mortality rates (4.0 vs 16.7 %, р=0.111) had no significant differences in groups of standard and angioplasty operations respectively. ACT was completed in 10 (16.7 %) patients only. There was true vein invasion in 12 of 18 patients with vein resection. рN+ (р=0.012) and angioplasty by itself (р<0.001) were found out as independent predictors of overall survival (OS). the median OS was 9.4 mo in patients with vein resection. in the group of standard operations, the median OS was 26.9 mo (р<0.001). The median OS in patients with vein resection and complete chemotherapy was 17.7 mo in contrast to 8.9 mo in those who did not receive chemotherapy (р=0.439). Conclusions. PDR with vein resection and incomplete chemotherapy cannot be regarded as a reasonable procedure. PDR with vein resection may be appropriate after efficient NACT.